The Conjunctive Analysis of Case Configurations: an Exploratory Method for Discrete Multivariate Analyses of Crime Data - Hart, Timothy C. (2008)
Derived from comparative approaches in both qualitative and quantitative research, the current study describes a simple exploratory technique for the multivariate analysis of categorical data. This technique is referred to as the conjunctive analysis of case configurations. After describing the logic and underlying assumptions of this conjunctive method, it is applied and illustrated in the study of the federal sentencing of drug offenders. The relative value of this conjunctive approach for purposes of exploratory data analysis and its overall utility as a method for confirmatory research are also discussed